PENGARUH KEJELASAN SASARAN ANGGARAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH MELALUI SISTEM PENGENDALIAN INTERN SEBAGAI VARIABEL INTERVENING (Studi Empiris pada Satuan Kerja Perangkat Daerah Kota Salatiga) - Ummu Kaltsum; Abdul Rohman (Diponegoro Journal of Accounting, 2014)
The present study aims to examine the effect of budget goal clarity on performance accountability government agencies. It also attempts toexamine whetherthe internal control system mediate the effect of the budget goal clarity government performance accountability. The research data collection using questionnaire survey. The questionnaire submitted to the Department of Revenue employees 50 Finance and Asset Management Regional Salatiga, 43 questionnaires ( 86 % ) returned complete and can be processed. The data collected were processed using path analysis to examine the effect of direct and indirect budget goal clarity on government performance accountability.These results indicate that the direct effect of the budget goal clarity government performance accountability. Budget goal clarity also significantly affect internal control system. Budget goal clarity indirectly affect the performance accountability of government agencies through the intervening variables of internal control systems.